Sustainability in education and environmental health to prevent Aedes spp: A literature review (2024)
Objective: Determine the state of knowledge in sustainable strategies used in health and environmental education to prevent the proliferation of the mosquito and vector of viral diseases, Aedes spp. Theoretical Framework: Concepts about the proliferation of the habitat of Aedes spp are addressed. mosquito that causes diseases such as dengue, Zika, chikunguya and yellow fever in various regions of the planet. Method: The PRISMA method was used, the words "environmental health" AND/OR "environmental education" AND/OR "environmental literacy" AND/OR "dengue" AND/OR "Aedes spp" were entered on the PubMed, Sciences Direct, Scopus and Virtual Health Library databases. Results and Discussion: One hundred and twelve documents were identified, out of which 65 articles were selected from 2008 to 2022 with the established level of suitability and classified into four areas: studies aimed at the community, research groups and government entities, studies related to the mosquito, and studies on uses of georeferencing as a tool. 20.8% of the literature reviews are from North America, 19.4% of the studies conducted in communities are from Latin America, and georeferencing studies begin to be evidenced from 2015. Research Implications: The ideal method to evaluate and apply sustainable strategies in communities is the cluster-randomized controlled trial. It is important to continue studying the behavior of the mosquito and the climatic, chemical, and biological factors that affect it, and using georeferencing tools to expand knowledge of the behavior of the mosquito in communities in terms of geographical distribution to create proliferation monitoring and prevention strategies. Originality/Value: The added value of the study is to address the health implications of climate change and how communities face the problem to prevent the introduction and proliferation of the mosquito without affecting the environment.